Curcumin ameliorates aging-induced blood-testis barrier disruption by regulating AMPK/mTOR mediated autophagy - Chen Xue; Zhenxing Yan; Wenjing Cheng; Dong Zhang; Rong Zhang; Hongwei Duan; Lihong Zhang; Xiaofei Ma; Junjie Hu; Jian Kang; Xiaojun Ma (PLoS ONE, 2025)
The blood-testis barrier (BTB) is composed of tight junctions (TJ) between adjacent Sertoli cells (SCs) and is crucial for sperm growth and development. Aging-induced TJ impairment is closely related to testicular dysfunction. Curcumin, a natural compound, has been widely demonstrated to have a wide range of pharmacological activities, but its regulatory effects on tight junction damage in the testis remain unclear. We here explored the effect of curcumin on TJ function and its underlying molecular mechanism by using D-galactose (D-gal)-induced mouse testis and mouse testicular SCs (TM4) aging models in vitro. In this study, D-gal increased the expression of aging-related proteins p16 and p21, whereas significantly decreased the expression of TJ proteins (ZO-1, Claudin-4, Claudin-7, and Occludin). In addition, curcumin restored the adverse effects of D-gal in the SCs. Autophagy is a degradation system for maintaining cell renewal and homeostasis. D-gal significantly decreased the autophagy level, whereas curcumin restored the effect of D-gal. Using chloroquine (CQ), an inhibitor of autophagy, and rapamycin (RAPA), an activator of autophagy, it was demonstrated that autophagy plays a key role in curcumin amelioration of TJ injury in testicular SCs. Further studies unveiled that autophagy activation was mediated through the AMPK/mTOR pathway. In conclusion, curcumin ameliorates aging-induced TJ damage through AMPK/mTOR signaling pathway-regulated autophagy. This study thus clearly identifies a novel action mechanism of curcumin in the treatment of age-related male reproductive disorders.